MATADOR PESTICIDE TOXICITY TEST ON KERPER FISH (cyprinus carpio) - VINA N VAN HARLING; Stefany Margareta Martono (SOSCIED, 2021)
A toxicity test is carried out to determine the death of the tested organism caused by the concentration of certain chemical compounds in the environment which is recorded as the value of lethal concentration (LC50). The main ingredients needed in this study are kerper fish (cyprinus carpio), water, and pesticides. The experiment was carried out 4 times, namely fresh, wayu 2 days, wayu 7 days, and wayu 9 days. 10 individual test animals were placed into each experimental container (vol. 4 liters). Water and test material were observed every 24 hours for 2 days, and during the experiment, the test animals were fed and oxygenated. The results showed that the resulting LC50 value for fresh was 3.55 x 10-4 ppm, the resulting LC50 value was 4.23 x 10-3 ppm, wayu 2 days was 8.69 x 10-3 ppm, wayu 7 days 5.68 x 10-3 ppm, and the resulting LC50 value for 9-day wayu is 1.026 x 10-2 ppm. The toxicity of matador pesticides against kerper fish that has been transmitted for 9 days is less effective. This happens because the pesticide is in direct contact with the air and the longer it is, the ability to kill the target animal is getting smaller. So if the pesticide is used, the toxicity will decrease so that the LC50 value will be higher